Cattaneo–Christov heat flux impacts on MHD radiative natural convection of Al2O3-Cu-H2O hybrid nanofluid in wavy porous containers using LTNE - Ahmed, Sameh E.; Mahdy, A.; Mansour, Mohamed A. (Nonlinear Analysis: Modelling and Control, 2023)
This paper aims to examine impacts of Cattaneo–Christov heat flux on the magnetohydrodynamic convective transport within irregular containers in the presence of the thermal radiation. Both of the magnetic field and flow domain are slant with the inclination angles Ω and γ, respectively. The worked fluid is consisting of water (H2O) and Al2O3-Cu hybrid nanoparticles. The enclosures are filled with a porous medium, and the local thermal nonequilibrium (LTNE) model between the hybrid nanofluids and the porous elements are considered. Influences of various types of the obstacles are examined, namely, horizontal cold elliptic, vertical elliptic and cross section ellipsis. The solution methodology is depending on the finite volume method with nonorthogonal grids. The major outcomes revealed that the location (0.75, 0.5) is better for the rate of the flow and temperature gradients. The higher values of H* causes that the solid phase temperature has a similar behavior of the fluid phase temperature indicating to the thermal equilibrium state. Also, the fluid-phase average Nusselt number is maximizing by increasing Cattaneo–Christov heat flux factor.
Keywords: Cattaneo–Christov heat flux; wavy containers; hybrid nanofluids; LTNE technique; natural convection; nonorthogonal grid; radiation